Single- and Multi-Network Hydrogels for Soft Electronics—A Review - Md Murshed Bhuyan; Nahid Hasan; Jae-Ho Jeong (Gels, 2025)
Soft or flexible electronics is a rapidly growing and pioneering research field, as it makes devices comfortable to use, especially in biomedical engineering. Both single- and multi-network hydrogels have diverse applications where the most significant one is in the building of soft electronics, including soft circuits, displays, sensors, batteries, and supercapacitors, electronic storage, electric skin, health monitoring devices, soft robots, and automotive. Three-dimensional printing of conductive gels/hydrogels facilitates the construction of soft electronics. This review illustrates the design, mechanism, and application of hydrogel in soft electronics. The current progress, scope of improvement, and future prospects of hydrogel-based soft electronics are also discussed. This review will provide a clear concept of the topic to researchers.